Spectroscopy and catalytic activity study of gold supported on barium titanate nanotubes for styrene epoxidation - Nepak, Devadutta; Srinivas, Darbha (Applied Catalysis A-General, 2016)
Gold (0.5-5 wt.%) supported on barium titanate nanotubes (Au/BaTNT) were prepared, characterized and for the first time, investigated as catalysts for selective oxidation of styrene with oxygen (O-2 or H-2 + O-2) and peroxides (H2O2 or TBHP). Conversion of styrene enhanced when H-2 was co-added to O-2 in the reactions. Au/BaTNT activated O-2 and H-2 and produced H2O2 in situ for use in oxidations. Peroxides were found better oxidants than O-2. At optimized conditions, styrene oxide selectivity of 80.1 wt.% at styrene conversion of 60.5 wt.% was achieved over Au(1 wt.%)/BaTNT using TBHP. Au particles (5.0-7.4 nm) were dispersed and decorated on the walls of BaTNT. They exhibited superior performance to the known Au catalysts in styrene oxidation. Reactive oxygen species formed during oxidation reactions were followed with in situ spectral characterizations (diffuse reflectance UV-vis and FT -Raman). Au/BaTNT was reusable in four recycles with little loss in catalytic activity. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Au Nanoparticles; reactive oxygen species; spectroscopy; Styrene Oxidation; Titanate nanotubes